UJI PATOGENISITAS JAMUR ENTOMOPATOGEN Beauveria bassiana Bals. TERHADAP WALANG SANGIT Leptocorisa acuta Thunb. PADA TANAMAN PADI - Elhanan B. Kastilong; Maxi Lengkong; Reity Engka (COCOS, 2022)
ABSTRACT Rice ear bug (Leptocorisa acuta) in rice is an important pest that can reduce rice production. One of the control techniques is a biological control technique that utilizes the entomopathogenic fungus B. bassiana. This study aimed to examine the pathogenicity of the entomopathogenic fungus B. bassiana against L. acuta. This research was carried out in May - July 2021 at the Laboratory of Biological Agents of the Kalasey Food and Horticultural Crops Protection and Quality Testing Center. The study used a completely randomized design (CRD) with 4 treatments which were repeated 3 times. The experimental treatment used doses with conidium density B. bassiana, namely conidium density 108 conidium/ml (A), 107 conidium/ml (B), 106 conidium/ml (C), and control (K). Based on the results of the study after the application of B. bassiana to L. acuta, the pathogenicity level of B. bassiana in infecting L. acuta on the tenth day had a difference where the treatment with conidium density of 108 conidium/ml was able to cause 72% mortality, in the treatment with a density of 107 conidium/ml can cause 57% mortality, and at a density of 106 conidium/ml it can cause 48% mortality. This difference in mortality could be due to the high concentration of spores used, thus affecting the existing mortality rate. The results of probit analysis showed that the LT50 value in the conidium density treatment of 108 conidium/ml reached 6.8 days; 107 conidium/ml reached 8.9 days; and 106 conidium/ml reached 11.9 days, with an LC50 value with a conidium density of 108 conidium/ml. The conclusion that can be drawn from this study is that the level of pathogenicity of the fungus B. bassiana infecting L. acuta occurred on the first day after application. Density treatment of 108 conidium/ml was able to cause the highest mortality, namely 72% mortality. The results of probit analysis showed that the fastest LT50 value was found in the treatment with a density of 108 conidium/ml which reached 6.8 days. LC50 is at a value of 7.8 or a concentration with a conidium density of 108 conidium/ml. Keywords : Rice (Oryza sativa L), Leptocorisa acuta, B. bassiana.